Effects of Fermentation Time and Brix on the Physicochemical Characteristics of Red Ginger Enriched Pineapple Honey Fermentate - Imanuel Bagus; Henny Parida Hutapea; Septiana Ambarwati (CV. Get Press Indonesia, 2025)
Pineapple is a local Indonesian fruit with limited processing applications. Developing a fermented herbal from pineapple with red ginger represent a potential product innovation to increase its value. This study aimed to determine the best formulation of pineapple-honey herbal fermentation with the addition of red ginger at different °Brix levels (20 and 30) and fermentation durations (2 and 4 weeks). Physicochemical and organoleptic characteristics were evaluated, including turbidity, °Brix, pH, ethanol content, vitamin C, and total soluble solids. Data were analyzed using one-way ANOVA and the Kruskal–Wallis test. The results showed that the addition of red ginger significantly affected turbidity, °Brix, vitamin C, and total soluble solids, but did not significantly affect pH and ethanol content. The best formulation based on organoleptic evaluation was obtained in samples fermented for 4 weeks at 30 °Brix. Overall, this study indicates that red ginger enrichment and fermentation parameters play an important role in improving the quality and sensory acceptability of pineapple-honey herbal fermentate.